2008
DOI: 10.1063/1.2988285
|View full text |Cite
|
Sign up to set email alerts
|

Community structures and role detection in music networks

Abstract: We analyze the existence of community structures in two different social networks using data obtained from similarity and collaborative features between musical artists. Our analysis reveals some characteristic organizational patterns and provides information about the driving forces behind the growth of the networks. In the similarity network, we find a strong correlation between clusters of artists and musical genres. On the other hand, the collaboration network shows two different kinds of communities: rath… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
(30 reference statements)
2
17
0
2
Order By: Relevance
“…However, broad spreading ranges were observed for nodes located in the network's core layers [2]. In addition, the ‫ܧ‬ ሺܺ ሻ normalized global diversity values produced by our proposed method were similar to participation coefficients reported by Teitelbaum et al [31], and the high global diversity of nodes that we observed were similar in terms of role with connector Figure 4; Bold, measurement result is inside the leading network group; Subscript, rank of network in the measurement.…”
Section: Preliminary Experimental Results and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, broad spreading ranges were observed for nodes located in the network's core layers [2]. In addition, the ‫ܧ‬ ሺܺ ሻ normalized global diversity values produced by our proposed method were similar to participation coefficients reported by Teitelbaum et al [31], and the high global diversity of nodes that we observed were similar in terms of role with connector Figure 4; Bold, measurement result is inside the leading network group; Subscript, rank of network in the measurement.…”
Section: Preliminary Experimental Results and Discussionsupporting
confidence: 86%
“…For example, global algorithms such as community detection algorithms can be used to analyze and obtain global information on community network structures, and to determine how factors such as position and node role [31] affect the degree to which spreaders distribute information or diseases throughout a network. We also plan to study strategies associated with multiple initial spreaders in networks.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the understanding of how collaboration between artists arises and its 2 influence in music similarity. For example, in [12] community detection algorithms were used to identify the role of musical leaders both in collaboration and similarity networks, distinguishing between local leaders, whose influence was restricted to a specific musical genre and connector leaders linking different musical styles. More recently, Park et al [13] investigated the cooccurence of classical music composers in CDs (compact discs) with the aim of understanding the centrality of western classical composers.…”
Section: Introductionmentioning
confidence: 99%
“…Given specific types of artist-related data one wants to visualize, a specific mapping must be done onto these data "containers". Nodes (or vertices) and edges are also central to the science of complex networks (Barabási, 2002), and a number of works in this field have recently brought some light onto the manifold intertwinements of musical artists networks (Cano et al, 2006), (Teitelbaum et al, 2008). There are several applications for visualizing artist networks as twodimensional connected graphs.…”
Section: Related Workmentioning
confidence: 99%